Peran Ekonomi Kreatif dalam Peningkatan Daya Saing UMKM Cirebon di Era Digital - Sudaryo, Yoyo (GEMA EKONOMI, 2025)
The Creative Economy has emerged as a powerful tool for enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), particularly in Cirebon, where digitalization is rapidly advancing. As MSMEs in Cirebon face challenges in adapting to the digital market, the role of digital marketing, e-commerce, and innovative product design through creative economy principles is crucial. This study aims to investigate how creative economy practices can enhance the competitiveness of MSMEs in Cirebon in the digital era. Using a qualitative research approach and a desk study, this study identifies key factors contributing to the successful adoption of digital technology by MSMEs in Cirebon. The study findings indicate that creative economy practices, particularly in digital marketing and product innovation, significantly improve market access and sales performance. However, challenges such as the digital skills gap and limited access to technology remain barriers. The study concludes with recommendations for enhancing policy support, training programs, and intersectoral collaboration to encourage the adoption of creative economy principles and digitalization for MSMEs.